Repo over the financial crisis - Adam Copeland; Antoine Martin (Federal Reserve Bank of New York, 2021)
This paper uses new data to provide a comprehensive view of repo activity during the 2007-09 financial crisis for the first time. We show that activity declined much more in the bilateral segment of the market than in the tri-party segment. Surprisingly, we find that a large share of the decline in activity is driven by repos backed by Treasury securities. Further, a disproportionate share of the decline in repo activity is connected to securities dealer's market-making activity in Treasury securities. In particular, the evidence suggests that at least part of the decline is not driven by clients pulling away from securities dealers because of counterparty credit concerns.
Keywords: G01; G23; E42; 330; repo; financial crisis; money markets